2016
DOI: 10.5430/ijhe.v5n3p79
|View full text |Cite
|
Sign up to set email alerts
|

Feel the Progress: Second-year Students’ Reflections on Their First-year Experience

Abstract: The aim of the present study was to explore first-year students' academic emotions and how they relate to their study progress. A mixed-method approach was used. The data consisted of deep interviews with 43 students. The number of their study credits was used as an indicator of their study progress. The results revealed that students expressed a wide variation of emotions. In addition, the study found significant relations between students' emotions and study progress. Results show that slow and fast-pace stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Although it is beyond the scope of this article to consider in any depth the implications of students' perceptions of success, other research has demonstrated that the extent to which students see themselves as successful has substantial implications for their wellbeing (e.g. stress, anxiety, feelings of worth), retention, approaches to study and university life, and future career prospects (Costello 2005;Reay, Crozier, and Clayton 2009;Hailikari, Kordts-Freudinger, and Postareff 2016). Thus, it is crucial to explore what shapes perceptions of success (both self-perceptions and perceptions of others), and to critically examine which categories of students are most easily ascribed the identity of successful student.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is beyond the scope of this article to consider in any depth the implications of students' perceptions of success, other research has demonstrated that the extent to which students see themselves as successful has substantial implications for their wellbeing (e.g. stress, anxiety, feelings of worth), retention, approaches to study and university life, and future career prospects (Costello 2005;Reay, Crozier, and Clayton 2009;Hailikari, Kordts-Freudinger, and Postareff 2016). Thus, it is crucial to explore what shapes perceptions of success (both self-perceptions and perceptions of others), and to critically examine which categories of students are most easily ascribed the identity of successful student.…”
Section: Resultsmentioning
confidence: 99%
“…For example, as noted earlier, the ways in which exceptionally high academic performance are normalised among some groups and anything other than excellence is regarded as failure can lead to stress, anxiety, fears of failure, shame and low self-worth (Walkerdine, Lucey, and Melody 2001). Additionally, constructions of success and success discourses shape, among other things: perceptions about who is most likely to be read by others as successful; students' approaches to learning and university life; feelings of belonging; career prospects; and wellbeing (Anderson, Kraus, and Keltner 2011;Jackson and Nyström 2015;Hailikari, Kordts-Freudinger, and Postareff 2016). In this particular paper, there is not space to consider in any detail the implications of students' perceptions of success.…”
Section: Introductionmentioning
confidence: 97%
“…Often, personal limits in their maturity level are exposed (e.g., poor study habits, high neuroticism) ( Clark 2005 ; Stein 2009 ). Hence, learning how to manage persistent confusion, unfamiliar negative emotions, and depression become formidable tasks ( Gall et al 2000 ; Hailikari et al 2016 ; Porteous and Machin 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The students who have better academic performance show more favorable perceptions about the university experience (Hailikari, Kordtsk-Freudinger, & Postareff, 2016). Good academic performance gives support to motivation and self-efficacy beliefs, leading students to new cycles of success and greater self-regulation of learning (Bandura, 1997;Hailikari et al, 2016). At the same time, high academic performance is associated with satisfaction with the course (Biner, Barone, Welsh, & Dean, 1997), understood as the subjective assessment that the student makes about his experience.…”
Section: Introductionmentioning
confidence: 99%